Ways of Addressing Problems of Quality Control of Synthetic Rubber Products at an International Level. (January 2018) - Boreiko, N.P.; Tkachenko, G.T.; Efremova, M.A.
The importance of developing GOST standard specifications for the quality control of different grades of synthetic rubber produced in Russia, incorporating standard elastic strength and rheometric characteristics, is shown. Here, ISO and ASTM test procedures must be used, as well as positive features of Russian technical documentation. The need for and the possibility of producing and certifying home-produced reference ingredients and carbon black are also shown. The creation of a unified base of reference materials (ingredients, carbon black, etc.) will make it possible to increase the reliability of product quality control at synthetic rubber, tyre, and mechanical rubber goods plants.